Makna Simbolik Pantun Banjar Samarinda dalam Teater Tradisional Sandima (Studi Kasus Pergelaran â€œPPKMâ€ Taman Budaya Kalimantan Timur) - Al Fayed, Muhammad; Simatupang, G. R. Lono Lastoro (Jurnal Bahasa, Sastra, dan Budaya, 2024)
This study aims to determine the origin of the banjar rhyme tradition, as well as to reveal the symbolic meaning of the Banjar Samarinda rhyme in the Sandima performance. This study uses a qualitative descriptive type of research that tries to explain, tell, describe, analyze and so on about the beginning of the Banjar pantun tradition in Samarinda, East Kalimantan in the Sandima traditional theater performance. The results of this study also reveal and find out the true meaning of the rhyme in Sandima's traditional theater performance entitled "PPKM" in East Kalimantan Cultural Park. His rhymes gave advice and messages to the public and especially the audience to maintain traditional arts, besides that the rhymes also represented the social conditions of the people of the city of Samarinda at that time.